Development of emission factors for pollutants from dominant fuelwood species in Northern South Africa - Khuthadzo Manyatsha; Burgert B Hattingh; Stuart Piketh; Frederik H Conradie; Joshua Edokpayi (Air Quality, Atmosphere & Health, 2026)
Residential biomass combustion in rural communities is recognised as a major contributor to air pollution, representing the second-largest source of gaseous emissions and the primary source of atmospheric particulate matter. In many African countries, including South Africa, residential emission inventories and air quality assessments rely largely on international emission factors (EFs), introducing considerable uncertainty due to regional differences in fuel characteristics, combustion technologies, and household energy-use practices. Generating locally derived EFs is therefore essential for improving the accuracy of emission inventories and supporting effective air quality management and climate policy development. This study quantified the EFs of CO₂, CO, NO, SO₂, and PM₁₀ from the combustion of the 12 predominantly preferred fuelwood species used for household energy in rural Limpopo Province, South Africa. Controlled combustion experiments were conducted using a traditional three-legged cookstove in a simulated village kitchen under laboratory conditions. The mean EFs determined for CO₂, CO, NO, SO₂, and PM₁₀ were 1389 ± 149, 131.38 ± 91.4, 1.22 ± 0.63, 5.16 ± 4.9, and 64.7 ± 76.3 g kg⁻¹, respectively. Modified combustion efficiency (MCE) exhibited a statistically significant negative association with the EFs of CO and SO₂, indicating that lower combustion efficiency was associated with higher emissions of these pollutants. In contrast, fuel moisture content was not significantly associated with the EFs of CO₂, NO, or PM₁₀, while no statistically significant relationship was observed between fuel nitrogen (N) content and NO EFs. Furthermore, no statistically significant differences were detected among the investigated fuelwood species in the individual EFs of CO₂, CO, NO, SO₂, and PM₁₀. This study provides the first laboratory-derived, species-specific EF dataset for the predominantly preferred fuelwood species used in rural Limpopo Province. The findings reduce uncertainties associated with the application of international default EFs and provide a robust basis for improving residential biomass emission inventories, air quality modelling, and the development of evidence-based air pollution mitigation and climate management strategies in South Africa and other regions with similar household energy-use patterns.

Air pollution and cardio-respiratory mortality in Limpopo, South Africa (2011–2020): evidence on population and seasonal vulnerability - Stephen Balaka Opiyo; Roelof Burger; Martha Nafula Balaka; Stuart Piketh (Air Quality, Atmosphere & Health, 2026)
Ambient air pollution is a growing public health concern in South Africa. However, the health impacts of ambient air pollution in the country remain largely unquantified, a gap that is consistently reflected in global systematic reviews. This study investigates the association between ambient air pollution and cause-specific mortality, cardiovascular (CVD), and respiratory disease (RD), in Limpopo province, South Africa, over a decade from 2011 to 2020, with the aim of unravelling population and seasonal vulnerability. Daily mortality data were sourced from Statistics South Africa, while ambient air pollutant concentrations (PM₁₀, PM₂.₅, SO₂, NO₂, and O₃) were retrieved from the South African Air Quality Information System. Time-series and quasi-Poisson regression models within a generalized additive model framework were employed to estimate relative risks (RRs) per interquartile range (IQR) increase in pollutant concentrations, adjusting for seasonality and meteorological covariates. A total of 73,167 CVD and 62,248 RD deaths were recorded during the study period. PM and O₃ emerged as the strongest predictors of excess mortality, with O₃ particularly linked to CVD mortality and PM to RD mortality. An interquartile range increase in O₃ was associated with a 0.3–7.5% increase in CVD and RD mortality across subgroups, while PM₂.₅ showed smaller but significant increases, ranging from 0.3 to 1.2% across subgroups for CVD and RD mortality. Notably, SO₂ and NO₂ exhibited weaker and more variable effects, often manifesting at delayed lags. Vulnerable populations, particularly women, older adults (65+), and certain outdoor-exposed workers, experienced greater mortality risks, highlighting the differential susceptibility of specific subgroups. Seasonal analysis revealed elevated mortality and pollutant concentrations during the cold compared to the warm period. Short-term exposure to ambient air pollution is associated with increased cardio-respiratory mortality in Limpopo Province, with stronger effects for ozone and particulate matter and heightened vulnerability during the cold season, highlighting the need for targeted public health and regulatory interventions.

Seasonal patterns and multidecadal trends in phytoplankton functional groups in the Benguela upwelling system off Namibia - Tebatso M. Moloto; Marié E. Smith; Thomas G. Bell; Stuart J. Piketh; Sandy J. Thomalla (Science of The Total Environment, 2025)

Prevalence of aeroallergen sensitization in a polluted and industrialized area: a pilot study in South Africa’s Vaal Triangle - Dorra Gharbi; Frank Harald Neumann; Jurgens Staats; Marinda McDonald; Jo-hanné Linde; Tshiamo Mmatladi; Keneilwe Podile; Stuart Piketh; Roelof Burger; Rebecca M. Garland; Petra Bester; Pedro Humberto Lebre; et al. (Environmental Monitoring and Assessment, 2025)
This pioneering study evaluates the prevalence of aeroallergens reactivity among atopic populations living in the Vaal Triangle Airshed Priority Area (VTAPA), South Africa. A total of 138 volunteers (51 males and 87 females), of African, colored, white, and Asian ethnicity, and with a mean (range) age of 22 (18–56) years were participating in the study. The study was conducted on the North-West University (NWU) campus in Vanderbijlpark/VTAPA. The International Study of Asthma and Allergies in Childhood questionnaire was utilized for pre-screening to identify individuals with probable allergic dispositions. Subsequently, skin prick testing was conducted using commercial aeroallergen extracts for all confirmed participants with allergy symptoms. One hundred six participants were clinically diagnosed with pollen and fungal spore allergies. The highest allergy prevalence was attributed to Cynodon dactylon ((L.) Pers) (Bermuda grass) (41.5%), followed by Lolium perenne (L.) (ryegrass), grass mix, and Zea mays (L.) (maize) (31.1%), respectively. Moreover, among the tree allergens, Olea (L.) (olive tree) was the most prevalent allergen (20; 18.8%), followed by Platanus (L.) (plane tree) (18; 16.9%). Among the weeds, 16 (15.1%) participants were allergic to the weed mix ( Artemisia ( L. ) (wormwood), Chenopodium (Link) (goosefoot), Salsola (L.) (saltwort), Plantago (L.) (plantain), and 11 (10.3%) to Ambrosia (L.) (ragweed)). Regarding the fungal spores, Alternaria (Fr.) (9; 8.5%) followed by Cladosporium (Link) (5; 4.7%) had the highest skin sensitivity. In this pilot study, our findings provide insights into the prevalence of allergic responses in the study population—underlining the strong impact of allergens of exotic plants—and contribute to the existing aerobiological data in South Africa.

Namib desert dust affects phytoplankton biomass in the Benguela upwelling region: Insights from first mesocosm study - Monray D. Belelie; Roelof P. Burger; Johanna R.C. von Holdt; Rebecca M. Garland; Gadaffi M. Liswaniso; Sandy J. Thomalla; Stuart J. Piketh (Continental Shelf Research, 2025)

Integrated assessment of strategies to reduce air pollution in the Vaal Triangle Priority Area, South Africa - Luckson Muyemeki; Roelof Petrus Burger; Stuart John Piketh; Peter Rafaj; Gregor Kiesewetter (Air Quality, Atmosphere & Health, 2022)

Rainwater Chemistry and Total Deposition of Acidity from the Northern Savanna to the Southern Coastal Fynbos of South Africa - Mpho K. Mompati; Stuart J. Piketh; Wenche Aas; Pieter G. Van Zyl; Jacobus J. Pienaar; Christopher J. Curtis (Water, Air, & Soil Pollution, 2022)

Characteristics of columnar aerosol optical and microphysical properties retrieved from the sun photometer and its impact on radiative forcing over Skukuza (South Africa) during 1999–2010 - Ayodele Joseph Adesina; Stuart Piketh; Raghavendra Kumar Kanike; Sivakumar Venkataraman (Environmental Science and Pollution Research, 2017)

Emissions management and health exposure: should all power stations be treated equal? - Ilze Pretorius; Stuart Piketh; Roelof Burger (Air Quality, Atmosphere & Health, 2017)

Arsenic-Based Warfare Agents: Production, Use, and Destruction - Barbara Radke; Linda Jewell; Stuart Piketh; Jacek Namieśnik (Critical Reviews in Environmental Science and Technology, 2014)

Concentrations, distributions and critical level exceedance assessment of SO2, NO2 and O3 in South Africa - Miroslav Josipovic; Harold J. Annegarn; Melanie A. Kneen; Jacobus J. Pienaar; Stuart J. Piketh (Environmental Monitoring and Assessment, 2010)

Spatial and temporal assessment of sources contributing to the annual austral spring mid‐tropospheric ozone maxima over the tropical South Atlantic - ROBERT J. SWAP; THOMAS A. SZUBA; MICHAEL GARSTANG; HAROLD J. ANNEGARN; LACKSON MARUFU; STUART J. PIKETH (Global Change Biology, 2003)
The primary source of the annual austral spring mid‐tropospheric ozone maxima over the tropical South Atlantic has generally been assumed to be biomass burning. However, ozone precursor emissions from biogenic, lightning, and anthropogenic sources in subequatorial Africa before and during the ozone peak are shown to be comparable, if not greater, in magnitude to regional biomass burning production. Moreover, an investigation of the spatial and temporal characteristics of these ozone precursor sources (i.e. vegetative and microbial activity, lightning‐induced generation, and anthropogenic emissions) suggests that these alternative sources can potentially make a substantial contribution to the seasonal ozone peak. This argument is supported by the practical limitations of atmospheric transport available to regionally produced ozone and ozone precursors.

Dry Deposition of Sulphur at a High-Altitude Background Station in South Africa - Mark Zunckel; Stuart Piketh; Tali Freiman (Water, Air, & Soil Pollution, 1999)